Davis' handbook of applied hydraulics - Zipparro, Vincent J. (McGraw-Hill, 1993)
Revised from cover to cover, this monumental Handbook reflects the rapid changes that have revolutionized the field and fully documents the tremendous influence of such dynamic changes as the correlation of field and laboratory testing programs, new design methods, and new materials, as well as new information on environmental concerns. Twelve sections are completely new to this edition; the remaining 16 sections have been condensed and updated to reflect current practice. And more tables and illustrations have been included than in previous editions. More than 34 experts have pooled their expertise to provide a complete handbook of the highest standards. They provide examples of many actual projects and emphasize coordination of field measurements of actual prototype behavior with theoretical analysis. Written for the practicing engineer, the book is organized in the same order that is usually followed in making regional plans for water use and control. Coverage ranges from basic hydraulics, reservoir hydraulics, and natural channels... through river diversion and the construction of reservoirs and dams... to pumped storage, navigation locks, irrigation and water, and waste water systems.